A biophysical and computational study unraveling the molecular interaction mechanism of a new Janus kinase inhibitor Tofacitinib with bovine serum albumin. Issue 6 (9th December 2016) - Abdelhameed, Ali Saber; Nusrat, Saima; Ajmal, Mohammad Rehan; Zakariya, Syed Mohammad; Zaman, Masihuz; Khan, Rizwan Hasan
Abstract: The interaction of a recently certified kinase inhibitor Tofacitinib (TFB) with bovine serum albumin (BSA) has been studied, by spectroscopic and molecular docking studies. Spectrofluorimetric measurements at 3 different temperatures (288, 298, and 310 K) showed that TFB quench the intrinsic fluorescence of BSA upon forming a nonfluorescent complex. The intrinsic fluorescence data showed that TFB binds to BSA with binding constant ( K b ) of approximately 10 4 M −1, affirming a significant affinity of TFB with BSA. The decrease in Stern‐Volmer quenching constant with increasing temperature exhibited the static mechanism of quenching. Negative value of Δ G (−6.94 ± 0.32 kcal·mol −1 ), Δ H (−7.87 ± 0.52 kcal·mol −1 ), and Δ S (−3.14 ± 0.42 cal·mol −1 ·K −1 ) at all 3 temperatures declared the reaction between BSA and TFB to be spontaneous and exothermic. Far‐UV circular dichroism spectroscopy results demonstrated an increase in helical content of BSA in the presence of TFB. Moreover, dynamic light scattering measurements showed that TFB resulted into a decrease in the hydrodynamic radii (from 3.6 ± 0.053 to 2.9 ± 0.02 nm) of BSA. Molecular docking studies confirmed that TFB binds near site II on BSA, hydrogen bonding, and hydrophobic interaction were involved in the BSA‐TFB complex formation. The present study characterizing the BSA‐TFB interaction could be significant towards gaining an insight into the drug pharmacokinetics and pharmacodynamics and also in the direction of rational drug designing with better competence, against emerging immune‐mediated diseases, ie, alopecia and rheumatoid arthritis. Abstract : Tofacitinib caused fluorescence quenching of BSA with binding constant of approximately 104·M −1 . Tofacitinib‐BSA interaction was spontaneous and exothermic. Increase in helical content of BSA was observed in the presence of Tofacitinib. Tofacitinib altered tertiary structure and decreased hydrodynamic radii of BSA. The BSA‐Tofacitinib interaction was by hydrophobic and hydrogen bonding at site II.